Exploring professionalization among Brazilian oral health technicians - Sanglard-Oliveira Carla; Werneck Marcos Azeredo; Lucas Simone; Abreu Mauro Henrique Nogueira Guimarães (BMC, 2012)
Abstract Professional dental auxiliaries emerged in the early 20th century in the United States of America and quickly spread to Europe and other regions of the world. In Brazil, however, oral health technicians (OHTs), who occupy a similar role as dental hygienists, had a long journey before the occupation achieved legal recognition: Brazilian Law 11.889, which regulates this occupation in the country, was only enacted in 2008. The aim of this paper is to review the literature on the professionalization of OHTs, highlighting the triggering, limiting and conflicting aspects that exerted an influence on the historical progress of these professionals in Brazil. We have tested Abbott's and Larson's theory on professionalization, against the history of OHTs. A number of different dental corporative interests exerted an influence over professionalization, especially in discussions regarding the permissible activities of these professionals in the oral cavity of patients. With primary health care advances in Brazil, the importance of these professionals has once again come to the forefront. This seems to be a key point in the consolidation of OHTs in the area of human resources for health in Brazil.